2014
DOI: 10.1063/1.4867615
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic heating effect of aggregated gold nanoparticle colloids

Abstract: Gold nanoparticles (GNPs) have been recently investigated intensively for potential hyperthermia treatment of malignant cancer cells in combination with radiofrequency (RF) electromagnetic (EM) fields/waves. However, many controversial results have been reported on whether GNPs can be heated by EM fields. It has been suggested that aggregated GNPs may be heated significantly by a RF field, which however has not been examined experimentally. This work proposes a novel electric treatment of mono-dispersed partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Liu et al suggested the possible modification of field distribution due to the change of boundary condition and dielectric properties. 86 Experimentally, Liu et al showed that the measured results could be explained by Hanson's model. 28,86 In addition, the sample holder could also modify boundary condition that attenuated the field strength.…”
Section: The Ionic Contributionmentioning
confidence: 95%
See 1 more Smart Citation
“…Liu et al suggested the possible modification of field distribution due to the change of boundary condition and dielectric properties. 86 Experimentally, Liu et al showed that the measured results could be explained by Hanson's model. 28,86 In addition, the sample holder could also modify boundary condition that attenuated the field strength.…”
Section: The Ionic Contributionmentioning
confidence: 95%
“…86 Experimentally, Liu et al showed that the measured results could be explained by Hanson's model. 28,86 In addition, the sample holder could also modify boundary condition that attenuated the field strength. 81 Considering that the presence of ions modifies both the conductivity and the dielectric properties, the contribution of ionic heating has to be carefully treated.…”
Section: The Ionic Contributionmentioning
confidence: 95%
“…However, for any point in the medium (z=1, 2, 3), the absorption increases to a peak point and then decreases with the attenuation factor. By using Equation (11), it can be predicted that the peak point takes place at α = 1/z. This observation quantified the optimal size of the tumor that a specific laser and nanoparticles can be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, side effects can also be suppressed. The research into nanomaterial-mediated hyperthermia has covered many energy sources, such as radiofrequency (RF) wave, 11,13 infrared (IR) laser, 14,15 and visible light laser. 16,17 Normally, the area of cancerous tissue shall be kept over 42 • C for a certain period so as to produce lethal effect to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation